The integration of flipped clasroom methods on ELT - Abidin, Ahmad Zaenal; Maulana, A.; Revan, A.; Tarihoran, Nafan (Journal of Language and Pragmatics Studies, 2025)
This study aims to explore the effectiveness of the Flipped Classroom method in improving English writing skills among students. The Flipped Classroom method allows students to learn basic theories and concepts independently through learning videos and online materials outside of class, while face-to-face time in the classroom is used for interactive discussions, writing exercises, as well as face-to-face feedback. This approach is expected to overcome the limitations of traditional learning methods that often do not provide enough time for students to practice writing intensively. Flipped classroom technology approach in this academic paper means a key pedagogical innovation that displays potential in reaching countless diverse learners in the classroom. Applying technology and engaging tasks that offer varied cognitive challenges for learners can help develop their higher-order thinking skills and encourage life-long learning. This method aligns with the evolving demands of 21st-century education, emphasizing student-centered learning, critical thinking, and active engagement. In the context of ELT, flipped learning offers a promising framework to enhance language acquisition by providing learners with more opportunities to practice and apply their skills in meaningful contexts.